Dual Task Timed Up-and-Go for Older Adults With and Without Balance Deficits. - Pohl, Patricia S.; Gras, Laura Z.; Bosch, Pamela R.; Ganley, Kathleen J.; Mayer, Jill (Physical & Occupational Therapy in Geriatrics, 2019)
Aims: Dual task conditions of the Timed Up-and-Go (TUG) add a cognitive (C-TUG) and a manual (M-TUG) task. The purpose of this study was to determine if balance ability differentially affected performance on the three TUG conditions. Methods: One hundred community-dwelling older adults participated. They performed the sharpened Romberg (SR) eyes open test as a measure of balance and the three TUG conditions. Results: Participants were 71.8 ± 7.8 years old. Across TUG conditions, those who completed the SR had faster TUG times than those who could not. Across groups, TUG times were faster than C-TUG and M-TUG times. Trends indicated that the C-TUG was challenging for those with the poorest balance, with an automaticity index twice that of the other groups and the lack of a correlation between the C-TUG and the TUG. Conclusions: As part of clinical assessment, the C-TUG may provide important information about balance, mobility, and cognition.